ESTIMATION OF RADIATION EXPOSURE TO THE ORAL MUCOSA DURING SUPERFICIAL RADIOTHERAPY OF CANCER OF THE LOWER LIP USING PERSONAL PROTECTIVE EQUIPMENT - E. V. Shevchenko; L. I. Galchenko; S. A. Smolin (Сибирский научный медицинский журнал, 2019)
The purpose of the study is to evaluate the effectiveness of the shielding of leaded rubber plates in superficial radiotherapy of lower lip cancer of stage I–II. Material and methods. A comparison was made of the timing and severity of oral mucosa and alveolar ridge damage in patients who used and did not use personal protective equipment. Experimental studies were carried out using a tissue-equivalent phantom and thermoluminescent detectors LiF activated by Mg and Ti. The summary doses received by the alveolar are calculated. Results and discussion. The total dose of X-ray radiation to the alveolar ridge in the absence of shielding is 64, 38 and 16 Gy for 1.0, 1.5 and 2.0 cm thick lip, respectively. The obtained values of the absorbed doses with personal protective equipment indicate a high shielding ability of the lead rubber used in the clinic. The use of shielding devices for superficial radiotherapy of lower lip cancer can improve the quality of life, reduces the duration and severity of radiation damage.